Role Of Ultrasonography in the Diagnosis and Follow-Up of Pediatric Eosinophilic Gastroenteritis: a Case Report and Review of the Literature - Savino, A.; Salvatore, R.; Cafarotti, A.; Cecamore, C.; De Sanctis, S.; Angelucci, D.; Mohn, A.; Chiarelli, F.; Pelliccia, P. (Ultraschall in der Medizin - European Journal of Ultrasound, 2011)
Eosinophilic gastroenteritis (EG) is a rare disease characterized by the infiltration of one or more layers of the digestive tract by eosinophilic leukocytes. The diagnosis is confirmed by histological examination of a characteristic biopsy, but radiological features are useful for diagnostic suspicion. We report the case of an adolescent boy with recurrent epigastric pain, nausea and vomiting, in whom sonographic features and eosinophilia of the peripheral blood suggested the diagnosis of EG. Moreover, we reviewed the radiological features of EG with particular regard to the role of sonography in the diagnosis and follow-up of EG, especially in children. We emphasize the utility of sonography in pediatric patients presenting with gastrointestinal symptoms, since it may provide useful information in a quick, inexpensive and noninvasive way. Ultrasonographic detection of features such as bowel wall thickness, ascites and peritoneal nodules may be largely suggestive of EG and may prevent other invasive exams and abdominal surgery. Ultrasonography can also be easily used in the follow-up of these patients, and may obviate the frequent and potentially dangerous exposure to radiation.
Keywords: eosinophilic gastroenteritis; ultrasound; children; radiological features